The upregulation of CLGN in hepatocellular carcinoma is potentially regulated by hsa-miR-194-3p and associated with patient progression - Cui, Zhongyuan; Wang, Jielong; Chen, Gang; Li, Dongliang; Cheng, Bianqiao; Lai, Yanhua; Wu, Zhixian (Frontiers in Oncology, 2023)
Background：Patients with hepatocellular carcinoma (HCC) have poor prognosis, especially in advanced stages. Targeted therapy is the main treatment for advanced HCC patients, but optimal targets of HCC are still lacking. The main purpose of this study is to screen novel potential prognostic markers and therapeutic targets. Methods: Firstly, differentially expressed genes（DEGs）in HCC from the Gene Expression Omnibus (GEO) database were identified. Then, the expression, significance in prognosis and potential mechanisms of DEGs were analyzed in GEPIA, TIMER, HPA, Kaplan Meier Plotter, CBioPortal, miRWalk, TargetScan and ENCORI databases. Immunohistochemical staining was used to verify the protein expression of the potential candidate genes. Results: The mRNA of MND1, STXBP6 and CLGN were significantly overexpressed in HCC (p< 0.01). HCC patients with higher mRNA levels of CLGN had poorer overall survival (OS), disease-free Survival (DFS), progression-free survival (PFS) and disease-specific survival (DSS) (p < 0.05). Higher mRNA level of MND1 was significantly correlated with poorer DFS in HCC patients (p< 0.05). There was no significant correlation between STXBP6 expression and prognosis of HCC (p> 0.05). Further analysis found that patients with higher mRNA expression of CLGN in advanced pathology stages had poorer prognosis (p< 0.01). In addition, CLGN protein was also highly expressed in HCC than in normal tissues. The mRNA levels of CLGN had no significant correlation with the abundance of six common tumor infiltrating lymphocytes in HCC (cor＜0.5). Moreover, the mutation rate of CLGN was less than 1% in HCC patients (10/1089). Finally, the expression level of the predicted hsa-miR-194-3p in HCC was significantly lower than in normal tissues (p＜0.05). The prognosis of HCC with low expression of hsa-miR-194 was poor (p＜0.05). Conclusion: The overexpression of CLGN in HCC is significantly associated with poor patient prognosis, especially in advanced stages, and may be regulated by hsa-miR-194-3p. These findings suggest that CLGN may be closely related to the progression of HCC, and is a potential therapeutic target and prognostic indicator for patients with advanced HCC.